Negative reviews online: an exploratory analysis of patient complaints about dental services in Western Australia. (23rd December 2021) - Kroon, M; Park, JS
ABSTRACT: Objective: Rates of online reviews are continually increasing. Coinciding with this, is the beneficial abundance of subjective information that is now available to patients. Such information can be persuasive in selecting a healthcare provider. This analysis of one‐and‐two‐star Google reviews received by dental practices within the Perth metropolitan region aims to identify common themes within dental practice complaints. Methods: This mixed‐methods study was conducted by gathering reviews from the 'Google review' feature, which have been published by users between 2013 and 2020. These data were then coded into recognised themes, and crucial quotes were selected and de‐identified creating a narrative about the themes present which formed the qualitative component of this research. Results: A total of 413 negative reviews were included in this study. From these, 1071 specific complaints were identified. Major themes identified included treatment issues, staffing, communication and professionalism, finance, and premise. Spread across these five themes were an additional thirty‐eight subthemes. Overall, treatment was a primary concern for patients, making up 37.1% of the results. Within the subthemes 'treatment dissatisfaction (unspecified)' was also high, at 23.1%. Conclusion: This study identified the most common complaints received by dental clinics on Google review within the Perth metropolitan area. Further investigation is required to provide supplementary data regarding factors that may influence complaint rates and types, such as the socio‐economic status of areas and geographical factors such as distance from the Perth metropolitan.